Mortality disparities: A comparison with the Haudenosaunee in New York State - Haring, Rodney C. (Cancer Health Disparities, 2018)
Identifying health status and disparities for Indigenous populations is the first logical step toward better health. We compare the mortality profile of the American Indian and Alaska Native (AI/AN) population with that of non-Hispanic whites in the Haudenosaunee Nations in New York State, the Indian Health Service (IHS) East region (Nashville Area) and the United States. Data from the linkage of IHS registration records with decedents from the National Death Index (1990–2009) were used to identify AI/AN deaths misclassified as non-AI/AN. Analyses were limited to persons of non-Hispanic origin. We analyzed trends for 1990–2009 and compared AI/AN and white persons in the Haudenosaunee Nations in New York State, IHS East region and the United States. All-cause death rates over the past two decades for Haudenosaunee men declined at a greater percentage per year than for AI/AN men in the East region and United States. This decrease was not observed for Haudenosaunee women with all-cause death rates appearing to be stable over the past two decades. Haudenosaunee all-cause death rates were 16% greater than that for whites in the Haudenosaunee Nations. The most prominent disparities between Haudenosaunee and whites are concentrated in the 25–44 year age group (Risk Ratio=1.85). Chronic liver disease, diabetes, unintentional injury, and kidney disease death rates were higher in Haudenosaunee than in whites in the Haudenosaunee Nations. The Haudenosaunee cancer death rate (180.8 per 100,000) was higher than that reported for AI/AN in the East (161.5 per 100,000).Haudenosaunee experienced higher rates for the majority of the leading causes of death than East AI/AN. These results highlight the importance of Haudenosaunee-specific data to target prevention efforts to address health disparities and inequalities in health.